From Blueprint to Belonging; Translating Social Inclusion in a Municipal Housing Pilot - Glotzbach, Anna-Lena; Nyassi, Sereh (My University, 2026)
Cities across the Nordics face a persistent gap between inclusive city ambitions and neighbourhood-level practice. This thesis examines how social inclusion is operationalised within an area-based planning process led by a municipal housing company and how challenges and tensions around roles, mandates and resources arise in that process. The study is a qualitative case study of a pilot area plan in Bergsjön, Gothenburg, a particularly vulnerable area according to the Swedish Police Authority. The mixed method approach includes semi-structured interviews, field notes from internal workshops and one public seminar as well as document analysis. The findings show that social inclusion is not a stable goal that travels intact from policy to practice. It is progressively translated and narrowed as it moves across strategic, programme and operational levels, shaped at each step by mandate boundaries, institutional accountability structures and resource constraints. While the municipal housing company has achieved sustained improvements in security, service quality and building conditions, harder-to-measure dimensions such as belonging, resident influence and structural integration remain largely rhetorical. Coordination between the municipal housing company and local actors, including schools, social services and civil society, is often informal and person-dependent, creating fragility under political and funding shifts. The analysis further reveals that social inclusion functions as a boundary object: sufficiently flexible to align actors around a shared agenda but unable to resolve the underlying divergences when concrete action requires genuine trade-offs. The thesis contributes empirical specificity to debates on operationalisation, translation theory and collaborative governance in Swedish urban planning and demonstrates that area-based social inclusion work is a project management challenge as much as a social policy challenge marked by mandate–capacity misalignment, coordination gaps and role ambiguity that are structural characteristics.
Keywords: Social inclusion, area-based development, municipal housing company, multi-actor collaboration, Sweden